Mormon midwife: the 1846-1888 diaries of Patty Bartlett Sessions - Sessions, Patty Bartlett, 1795-1892, editor; Smart, Donna Toland, editor; Utah State University Press, publisher (Colorado State University. Libraries, 1997)
Patty Session's 1847 Mormon Trail diary has been widely quoted and excerpted, but her complete diaries chronicling the first decades of Mormon settlement at Salt Lake City have never before been published. They provide a detailed record of early Mormon community life from Illinois to Utah through the eyes of Mormondom's most famous midwife. They also recount her important role in women's social networks and her contributions to community health and Utah's economy, to pioneer education and horticulture. Patty Sessions assisted at the births of hundreds of early Mormons and first-generation Utahans, meticulously recording the events. Shed had an active role in the founding of the Relief Society and health organizations. She spoke in tongues and administered spiritually as well as medically to the ill. Her diaries are a rich resource for early Mormon and Utah history.--Provided by publisher.
Foreword / Maureen Ursenbach Beecher -- Preface -- Introduction -- Diary One, 1846-1848 -- Diary Two, 1849-1850 -- Diary Three, 1851-1852 -- Diary Four, 1853-1855 -- Diary Five, 1856-1862 -- Diary Six, 1862-1880 -- Diary Seven, 1884-1888 -- Epilogue -- Appendix One: Account Book -- Appendix Two: Children's Families -- Appendix Three: Braiding School Minutes.
Keywords: Women pioneers -- West (U.S.) -- Diaries; Midwives -- West (U.S.) -- Diaries; Mormon women -- West (U.S.) -- Diaries; Frontier and pioneer life -- West (U.S.); Nauvoo (Ill.) -- Biography; Sessions, Patty Bartlett, 1795-1892 -- Diaries